Some estimates of special classes of integrals - Malyutina, T. I. (Mathematical Modelling and Analysis, 2000)
We study the integrals f b a f (t) exp(i| ln rt|σ) dt and obtain asymptotic formula for these functions of non‐regular growth. This is a peculiar kind of the theory asymptotic expansions. In particular, we get asymptotic formulae for different entire functions of non‐regular growth. Asymptotic formulas for Levin‐Pfluger entire functions of completely regular growth are well‐known [1]. Our formulas allow to find limiting Azarin's [2] sets for some subharmonic functions. The kernel exp(i| ln rt|σ) contains arbitrary parameter σ > 0. The integrals for σ ∈(0, 1), σ = 1, σ > 1 essentially differ. Our arguments can apply to more general kernels. We give a new variant of the classic lemma of Riemann and Lebesgue from the theory of the transformation of Fourier.Specialiųjų integralų klasių įverčiaiSantrauka. Darbe nagrinėjami integralai f b a f (t) exp(i| ln r|σ) dt ir tiriamos šių nereguliaraus augimo greičių funkcijų asimptotinės formulės. Gautos naujos asimptotinės formulės, leidžiančios rasti Azarino aibes kai kurioms subharmoninėms funkcijoms. Branduolys exp(i| ln rt|σ) priklauso nuo vieno parametro σ > 0. Trys atvejai, kai 0 < σ < 1, σ = 1 ir σ > 0, yra esminiai skirtingi. Darbo metodika gali būti naudojama ir bendresniems branduolių atvejams. Įrodytas naujas Rimano ir Lebego lemos variantas, kuris naudojamas Furje transformacijos teorijoje.First Published Online: 14 Oct 2010